1978
DOI: 10.1113/jphysiol.1978.sp012344
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of slow discharges of sheep carotid artery.

Abstract: 5. When procaine was added, or Ca replaced by Mn or Mg, conductance was lower both at rest and on depolarization, and the increase on depolarization often underwent slow inactivation which it never did in simple Ca containing solutions.6. The results indicate that a slowly inactivated inward current dependent on Ca, Mn or Mg was largely responsible for the slow discharges, and that procaine, Mn or Mg assisted the discharges by reducing the normal rapid outward-rectifying K conductance and allowing it to inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
(39 reference statements)
2
11
0
Order By: Relevance
“…The observations made are in accord with those made on sheep carotid arteries (Keatinge, 1968(Keatinge, , 1978 and suggest that these arterioles, if they are close to the point of their origination from the middle cerebral artery (see Hill, Hirst, Silverberg & van Helden, 1986), possess two distinct inward calcium currents, an outward rectifying potassium current and a slow calcium-activated potassium current.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…The observations made are in accord with those made on sheep carotid arteries (Keatinge, 1968(Keatinge, , 1978 and suggest that these arterioles, if they are close to the point of their origination from the middle cerebral artery (see Hill, Hirst, Silverberg & van Helden, 1986), possess two distinct inward calcium currents, an outward rectifying potassium current and a slow calcium-activated potassium current.…”
Section: Introductionsupporting
confidence: 84%
“…Properties of the slow after-hyperpolarization -effect of substituting barium for calcium As has been pointed out, action potentials recorded from middle cerebral arterioles were often followed by a slow after-hyperpolarization which was abolished by calcium removal and not detected at membrane potentials some 20-30 mV negative of rest (see also Keatinge, 1978). In voltage clamp experiments a small amplitude persistent outward current was occasionally detected following the larger membrane depolarizations (Fig.…”
Section: Effects Of Divalent Cations and Calcium Antagonistsmentioning
confidence: 63%
See 2 more Smart Citations
“…Recently Haeusler (1978), discussing the properties of the muscle membrane of the rabbit pulmonary artery, stated that TEA depolarizes the membrane presumably by suppression of K-conductance. Keatinge (1975Keatinge ( , 1978, studying the effect of procaine on the sheep carotid artery, found that spike generation in the presence of procaine is mainly due to depolarization of the membrane by suppression of K-permeability, and that these effects of procaine are still observed in Ca-free EGTA containing solution. He postulated that the spike generated from the carotid artery is due to activation of the Na-channel.…”
Section: Discussionmentioning
confidence: 99%